Meta Analisis : Pengaruh Pembelajaran Kearifan Lokal untuk Meningkatkan Kemampuan Berpikir Kritis - Sabat, Dian Ristiani; Sudiatmika, AAIA Rai; Suma, I Ketut; Suardana, I Nyoman (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
This research aims to present a comprehensive review of the influence of learning local wisdom on improving critical thinking skills, by conducting a meta-analysis of a number of empirical studies through appropriate articles. The method used in the research is the meta-analysis method by reviewing journal articles found according to the topic, then the meta-analysis stages are adjusted to the meta-analysis research steps. The results of the analysis provide a broader picture of the impact of local wisdom learning on empirical aspects related to meta analysis of educational levels, increasing N-Gain, meta-analysis of objectives, statistical analysis, research design and measuring effect size. The meta-analysis results show that learning local wisdom significantly contributes to improving overall critical thinking abilities. These findings strengthen the argument that educational curricula must contain elements of local wisdom to improve students' critical thinking skills and can help decision makers in the field of education make policies and learning practices that are more relevant to the local cultural context.